A solar-driven 5th generation district heating and cooling network with ground-source heat pumps: a thermo-economic analysis. (January 2022) - Calise, Francesco; Cappiello, Francesco Liberato; Dentice d'Accadia, Massimo; Petrakopoulou, Fontina; Vicidomini, Maria
Highlights: Evaluation of a 5 th generation bidirectional heating/cooling network for 50-buildings Water-to-water, ground heat pumps and a photovoltaic field are designed Primary energy saving and avoided CO2 emissions are 76% and 64% High payback period due to costs of excavation, pipe laying and heat pumps Abstract: District Heating and Cooling is considered an efficient solution to address the thermal energy demand of the building sector and reduce its environmental impact. In this paper, a 5 th generation bidirectional heating/cooling network is designed and modelled. The network is coupled with water-to-water heat pumps, ground heat pumps and a photovoltaic field and is designed to meet the energy requirements of a 50-building district in the city of Leganés (Madrid). All components are modelled in TRNSYS 18. The studied network achieves a primary energy saving index of 64% and reduces the CO2 emissions by 76% relative to the current situation. The economic analysis of the system results in the relatively long payback period of 33 years, mainly due to the high costs of excavation and the installation of the heat pumps and pipes. With the current design, the photovoltaic field meets only 30% of the electricity demand of the district. However, additional energy storage could help align the power production with the actual power demand better and avoid grid balancing issues. The inclusion of other types of thermal energy consumers would also enhance the performance of the network by increasing the simultaneity between cooling and heating demands.